A Comparative Density Functional Theory and Density Functional Tight Binding Study of Phases of Nitrogen Including a High Energy Density Material N8 - Nicholas Capel; Devang Bharania; Sergei Manzhos (Computation, 2015)
We present a comparative dispersion-corrected Density Functional Theory (DFT) and Density Functional Tight Binding (DFTB-D) study of several phases of nitrogen, including the well-known alpha, beta, and gamma phases as well as recently discovered highly energetic phases: covalently bound cubic gauche (cg) nitrogen and molecular (vdW-bound) N8 crystals. Among several tested parametrizations of N–N interactions for DFTB, we identify only one that is suitable for modeling of all these phases. This work therefore establishes the applicability of DFTB-D to studies of phases, including highly metastable phases, of nitrogen, which will be of great use for modelling of dynamics of reactions involving these phases, which may not be practical with DFT due to large required space and time scales. We also derive a dispersion-corrected DFT (DFT-D) setup (atom-centered basis parameters and Grimme dispersion parameters) tuned for accurate description simultaneously of several nitrogen allotropes including covalently and vdW-bound crystals and including high-energy phases.